Effectiveness of the Combination of Green Betel Leaf Extract (Piper betle) and Mint Leaf (Mentha piperita) as Antibacterials against Streptococcus mutans - Inka Kandida; Mayang Tari; Awalul Fatiqin (Pandawa Institute, 2023)
The content of betel leaf (Piper betle) includes essential oils, alkaloids, flavonoids, phenols, and steroids. Flavonoid compounds in P. betle show a mechanism of action in damaging bacterial cell proteins and disrupting irreparable membranes. On the other hand, mint leaves (Mentha piperita) contain essential oil ranging from 1-2%, with menthol content around 80-90%, as well as mentone, d-piperitone, hexanol phenyl acetate, ethyl amyl carbinol, and neomenthol. The aim of this study is to determine the effectiveness of the combination of P. betle extract and M. piperita extract in inhibiting the growth of Streptococcus mutans (S. mutans) bacteria using the well diffusion method. Extraction of P. betle and M. piperita extracts were performed using the maceration method. The extraction results showed a yield of 24.94% for the P. betle extract and 35.39% for the M. piperita extract. The antibacterial testing against S. mutans showed an inhibition zone of 21.83 ± 1.58 mm for the single P. betle extract (ML), 11.2 ± 1.00 mm for the M. piperita (GBL), and 11.76 ± 0.57 mm for the combination extract (GBL/ML). There is an influence of the combination of P. betle and M. piperita extracts on the antibacterial effectiveness against S. mutans, although the inhibition zone of the P. betle is larger, measuring 21.83 ± 1.58 mm.